BIOLOGICAL ACTIVITY OF SOIL IN SOWING OF WINTER WHEAT DEPENDING ON PREDECESSORS IN FOREST-STEPPE THE LEFT-BANK - Корецький, О. Є. (Scientific Progress & Innovations, 2013)
Dependence of biological activity of soil under crops of winter wheat from predecessors and a set of cultures in short-term crop rotations is investigated. Positive influence of of leguminous predecessors of esparcet, peas and a soya on biological activity of soil microorganisms at crops of winter wheat in crop rotations from a part of grain crops 50; 66,7; 100 % is revealed. During researches it has been established, that accommodation of winter wheat after predecessors of winter wheat and pair black conducted to decrease in intensity of biochemical processes in a superficial layer of soil on 17–35 % compared with leguminous predecessors.